2023
DOI: 10.1002/jmv.29198
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics, clinical manifestations, and mental health status of human mpox cases: A multicenter cross‐sectional study in China

Leiwen Fu,
Bingyi Wang,
Ke Wu
et al.

Abstract: Human mpox is occurring worldwide, however, evidence from the Asian Pacific Region is limited. In this multicenter cross‐sectional study, information of confirmed mpox cases diagnosed between June 1 and July 31, 2023 in China. Information included demographic and epidemiological characteristics, and clinical manifestations, laboratory results, and mental health status of mpox cases. A total of 115 confirmed mpox cases were enrolled. All cases were men. A total of 102 (90.3%) identified as homosexual. The media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…33,34 However, it's noteworthy that one patient identified as heterosexual, consistent with a recent study that has identified some heterosexual patients. 35 This suggests that mpox may be spreading beyond high-risk groups to the general population, highlighting the need to update guidelines for screening and epidemiological investigations.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 However, it's noteworthy that one patient identified as heterosexual, consistent with a recent study that has identified some heterosexual patients. 35 This suggests that mpox may be spreading beyond high-risk groups to the general population, highlighting the need to update guidelines for screening and epidemiological investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Un 56,5 % de los pacientes eran VIH positivos, de los cuales 92,3 % estaban recibiendo terapia antirretroviral (TAR), concluyendo que los pacientes infectados también con VIH tenían más probabilidades de tener ansiedad, de allí la importancia de un abordaje integral del paciente. (44) El temor subsecuente de la comunidad LGBTIQ+ a la discriminación podría generar que personas sintomáticas no acudan a buscar asistencia médica, que generaría una transmisión inconsciente. De allí la necesidad que los profesionales abocados a la salud mental centren sus esfuerzos en brindar consejos de salud y alentarlos a vacunarse contra la viruela símica como medida profiláctica.…”
Section: Desarrollounclassified
“…By June 2023, two indigenous cases were documented in Beijing. From then on, the disease began to emerge in other regions of China [3]. The current outbreak of mpox has a different clinical manifestation from the classic form, with lesions mainly localized in the anal and genital regions and high-risk sexual contact being the primary transmission route [4].…”
Section: Introductionmentioning
confidence: 99%
“…The current outbreak of mpox has a different clinical manifestation from the classic form, with lesions mainly localized in the anal and genital regions and high-risk sexual contact being the primary transmission route [4]. According to a multicenter crosssectional study conducted in China, individuals living with HIV comprised 56.5% of the mpox population [3]. The overall mortality rate of the outbreak is approximately 1 per 1000.…”
Section: Introductionmentioning
confidence: 99%